PENGENALAN EKONOMI DAN BISNIS ISLAM DAN EDUKASI PERUBAHAN PERILAKU MASYARAKAT PERKOTAAN DALAM MASA PANDEMI COVID-19 DI KELURAHAN PASIR JAYA, KECAMATAN BOGOR BARAT, KOTA BOGOR - Rully Trihantana; Ermi Suryani; Tiar Cipta Prasetia (SAHID EMPOWERMENT JOURNAL, 2022)
Community service is not only carried out for rural communities in the midst of the Covid-19 pandemic, but also for urban communities. Urban communities such as Bogor City, especially in an urban village in Bogor City, still need behavior change education to increase the number of individuals, families, institutions and communities who comply with health protocols, especially 3M. This was carried out in the Pasir Jaya Village, West Bogor District, Bogor City. This community service involves the participation of all levels of society, without exception, to change behavior in dealing with the Covid-19 pandemic. Behavior changes which are often known as 3M (wearing masks, keeping a distance and avoiding crowds, and washing hands with soap) are carried out by the method of educational activities carried out from July to August 2020. These educational activities show that the community has complied with the implementation health protocol 3M by carrying out at least 3 (three) disciplinary behaviors, namely: Wearing a mask Washing hands Maintaining distance and avoiding crowds. At the same time, the introduction of Islamic economics and business to the public was carried out.